1995
DOI: 10.1111/j.1365-3040.1995.tb00629.x
|View full text |Cite
|
Sign up to set email alerts
|

Scaling gross ecosystem production at Harvard Forest with remote sensing: a comparison of estimates from a constrained quantum‐use efficiency model and eddy correlation

Abstract: Two independent methods of estimating gross ecosystem production (GEP) were compared over a period of 2 years at monthly integrals for a mixed forest of conifers and deciduous hardwoods at Harvard Forest in central Massachusetts. Continuous eddy flux measurements of net ecosystem exchange (NEE) provided one estimate of GEP hy taking day to night temperature differences into account to estimate autotrophic and heterotrophic respiration. GEP was also estimated with a quantum efficiency model hased on measurement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(62 citation statements)
references
References 53 publications
(55 reference statements)
2
58
0
Order By: Relevance
“…Using a threshold number of 50% of the buds on the trees opening, we estimate that bud-break occurs between 4 and 7 d sooner in trees in the warmed area. This translates to a 3-4% increase in the mean growing season length of 161 d reported for deciduous stands at the Harvard Forest (34). A slightly longer growing season may be interacting with greater nitrogen availability to enhance plant productivity and carbon storage.…”
Section: Resultsmentioning
confidence: 95%
“…Using a threshold number of 50% of the buds on the trees opening, we estimate that bud-break occurs between 4 and 7 d sooner in trees in the warmed area. This translates to a 3-4% increase in the mean growing season length of 161 d reported for deciduous stands at the Harvard Forest (34). A slightly longer growing season may be interacting with greater nitrogen availability to enhance plant productivity and carbon storage.…”
Section: Resultsmentioning
confidence: 95%
“…In addition, the most commonly developed relationships (such as those between spectral band combinations and LAI, volume or total aboveground biomass) are nonlinear and saturate at approximately 100 Mg ha -1 (Cohen and Spies 1992) and an LAI greater than 3 . Likewise, synthetic aperture radar (SAR) has been found to be insensitive to differences in forest biomass above 150 Mg ha -1 (Waring et al 1995) which is generally well below that observed in temperate forests.…”
Section: Introductionmentioning
confidence: 99%
“…TEC uses a universal e* with a value of 1.8 gC MJ À1 observed for C3 species in field (Waring et al, 1995) and already employed by 3-PG model (Landsberg and Waring, 1997). However, as leaf photosynthetic rates of C4 species are greater than those of C3 species (Jones, 1992;Pearcy and Ehleringer, 1984;Prince and Goward, 1995;Baldocchi, 1994).…”
Section: Development Of Global Terrestrial Ecosystem Carbon Flux (Tecmentioning
confidence: 99%